The effects of smoking addiction and physical activity on some respiratory functions in female university students - M.F. Bilici; A. Genç (IP Iermakov S.S., 2020)
Aim:The aim of this study is to examine the effects of smoking addiction and physical activity on some of the respiratory functions in female university students. Methods:103 female students who did not have any health problems, who had an average age of 20,00 (years), average height of 163,6 (cm) and average weight of 55,88 (kg) participated in the study voluntarily. Female students who participated in the study were grouped according to their states of having smoking addiction (athlete, sedentary) and doing exercise (athlete, sedentary) and later some of the respiratory functions were measured. SPSS program was used in the statistical analysis of the data obtained. Shapiro-wilk test was used to find out the normality distribution of the data. Kruskal Wallis test was used in the analysis of the data which were not normally distributed and Mann-Whitney U test was used in sub-groups. Results: FVC(Forced Vital Capasity), FEV1(Forced Expiratory Volume in 1 second), FEV1(Forced Expiratory Volume in 1 second )/FVC(Forced Vital Capasity), PEF(Peak Expiratory Flow), FEF25-75% (Forced Expiratory Flow at 25-75% ), VC(Vital Capacity) and MVV(Maximal Voluntary Ventilation) values of the female students who were engaged in sports were found to be significantly higher when compared with the groups which were not engaged in sports (p<0,05). Conclusion:In addition, in terms of the variable of smoking addiction, statistically significant difference was found between the FEV1, FEV1/FVC(%), PEF (L/s), FEF25-75% (L/s) and MVV values of the female student groups in favour of sedentary and athlete students who were not smokers.